(untitled) (Swiss Medical Weekly, 2016)
QUESTIONS UNDER STUDY: Alzheimer-type amyloid-β (Aβ) pathology was reported in brains of individuals developing iatrogenic Creutzfeldt-Jakob disease (iCJD) after treatment with human cadaveric growth hormone, and interpreted as evidence of human transmission of Aβ by the treatment. Here we investigated the prevalence of Aβ pathology in other instances of iCJD related to dura mater grafts. METHODS: By use of immunohistochemistry for Aβ, we investigated seven brains of patients (age range 28–63) who succumbed to iCJD after dural grafting, which had been applied by means of neurosurgery between 11 and 25 years before death. For control, we examined a series of 21 brains of age-matched (40–63 years) patients with sporadic CJD (sCJD) and an additional series of 81 sCJD cases (55–85 years) with the same methods. RESULTS: In five of seven iCJD brains, Aβ was deposited in meningeal vessels as congophilic amyloid angiopathy and brain parenchymal plaques. This was significantly (p <0.001) more frequent than in the age-matched sCJD controls and in the usual sCJD series. CONCLUSIONS: We conclude that congophilic amyloid angiopathy and brain parenchymal Aβ plaques are frequent in iCJD after dural grafting. The presence of Aβ pathology in young individuals is highly unusual and suggests a causal relationship to the dural grafts. Further studies will be needed to elucidate whether such pathology resulted from the seeding of Aβ aggregates from the grafts to host tissues.